Social Development of Children with Single Parent Style - Setiawan, Usep; Mukti, Saepul; Supendi, Dede (World Psychology, 2025)
This study focuses on the social development of children raised in single-parent families in Pasawahan District, Purwakarta, West Java. The background of this research is driven by the increasing number of single-parent families in Indonesia, raising concerns about the potential impact on the social development of the involved children. The aim of this study is to analyze the influence of single-parent parenting on children's social development, evaluate the relationship between such parenting and children's social well-being, and develop intervention programs aimed at enhancing the social welfare of children from single-parent families. The research methodology employed includes a literature review, quantitative surveys, in-depth interviews, and observational monitoring. The study also draws on various concepts and theories, such as the Parental Involvement Theory, Social Support Theory, and Resilience Theory, to understand how these factors influence children's social development within the context of single-parenting. The findings indicate that while single-parenting presents unique challenges to children's social development, targeted intervention programs can significantly improve their social outcomes. Further analysis underscores the importance of a comprehensive support system to promote the social well-being of children in single-parent families and the implications for policy formulation and program development. This research also aims to support more effective policies and strategies in enhancing the welfare of children from single-parent families in Indonesia.